Necessary and sufficient conditions for the absolute instability of solutions of linear differential-difference equations with self-adjoint operator coefficients - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
For linear differential-difference equations of retarded and neutral types with infinitely many deviations and self-adjoint operator coefficients, we present necessary and sufficient conditions for the absolute instability of the zero solutions.